Fused Deposition Modeling(FDM) Custom Internal Filling Structural Mechanics Simulation - Japrin, Sabri; Ibrahim, Mustaffa (Research Progress in Mechanical and Manufacturing Engineering, 2022)
FDM is a very complex method that relies on many factors which including the characteristics of the heat source scanning techniques, powder bed, and material properties makes several problems remain such as require too much printing time and material used. The objective of this study was to simulate and optimize internal structure infill so that the weight and printing duration of the 3D structure can be reduced and compare the mechanical performance between ABS filament and PLA filament using COMSOL Multiphysics. The carabiner infill structure used two different infill patterns and manipulating different densities of the same material using slicer software. At the end of the result, the printing time and filament used can be reduced by 17%. This shows that the custom infill is much more economical in terms of material cost compared to the solid infill. The study also finds that different material filaments produced different displacements. ABS filament produces longer displacement compared to PLA filament due to it is a bit flexible and therefore less brittle than PLA. Even though ABS material had higher displacement but in the real-life industry, PLA filament is easier to be printed because PLA nozzle temperatures are lower compared to ABS filament.